Soldati e neuropsichiatria nell'Italia della Grande Guerra Controllo militare e pratiche assistenziali a confronto (1915 - 1918) - Romano, Marco (Premio Tesi di Dottorato, 2020)
Against the backdrop of a critical reflection on the psychiatric concepts of organicism and predisposition to mental illness, the research investigates the relationship between psychiatry and the Great War from a perspective that considers the complexity of the orientations assumed by both the Italian alienists on war pathologies and the health practices implemented towards soldiers. The study highlights the comparison/clash between two totally different approaches forced to coexist during the conflict: on one side, the one from military psychiatry, and on the other the distinctive one from civil asylums. The two perspectives were not always clearly separated, but it is possible to detect a constant tension between the duties towards the war effort and the professional ethics dictated by the neuropsychiatric discipline.